Madžarska narodna skupnost v času osamosvojitve Slovenije in ustavnih sprememb ter sprejetja nove ustave (1989–1991) - Göncz, László (Studia Historica Slovenica, 2022)
The article presents the development of the constitutional status of the Hungarian national community, i.e. of the autochthonous national communities, in the period of democratisation of the Slovene society and Slovenia's gaining of independence (1989–1991), as well as the attitude of the Prekmurje Hungarians towards the independence process. The topics concerned confirm that the general democratisation of society and the process of Slovenia's independence had direct and indirect impacts on the life and the legal and social status of the members of the Hungarian (as well as Italian) national community. The above processes also affected the political engagement and participation of the Hungarian national community and had a significant impact on the formation and activities of its organisations. The article reveals that also the organisations of Prekmurje Hungarians played a part in the endeavours for the official recognition of Slovenia's independence by Hungary.
Keywords: 1989–1991; človekove pravice; Madžari; narodne manjšine; osamosvojitev; plebiscit; Pravna zgodovina; Slovenija; Ustava Republike Slovenije; ustavni amandmaji; ustavno pravo